2011
DOI: 10.1039/c1mb05242j
|View full text |Cite
|
Sign up to set email alerts
|

Bisphosphonates as radionuclide carriers for imaging or systemic therapy

Abstract: Bisphosphonates (BP's), biologically stable analogs of naturally occurring pyrophosphates, became the treatment of choice for pathologic conditions characterized by increased osteoclast-mediated bone resorption, namely Paget's disease, osteoporosis and tumor bone disease. Moreover, the clinical success of BP's is also associated with their use in (99m)Tc-based radiopharmaceuticals for bone imaging. In addition to the successful delivery of (99m)Tc (γ-emitter) to bone, BP's have also been used to deliver β(-)-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
54
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 134 publications
0
54
0
Order By: Relevance
“…A large number of patients suffering from cancers develop disseminated skeletal metastases at the advanced stage of their disease [1][2][3]. It is reported that ∼ 80% of these patients experience severe bone pain, which is the most common symptom manifested in metastatic skeletal carcinoma [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of patients suffering from cancers develop disseminated skeletal metastases at the advanced stage of their disease [1][2][3]. It is reported that ∼ 80% of these patients experience severe bone pain, which is the most common symptom manifested in metastatic skeletal carcinoma [4].…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that ∼ 80% of these patients experience severe bone pain, which is the most common symptom manifested in metastatic skeletal carcinoma [4]. In addition to excruciating pain, other associated complications such as loss of mobility, skeletal fractures, hypercalcemia and spinal cord or nerve root compression severely impair the quality of life experienced by these patients [1][2][3][4][5][6]. Such patients are subjected to palliative care with the primary objective being alleviation of the pain resulting in improvement of the quality of life [7].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the well-established clinical use, directly radiolabeled bisphosphonate complexes suffer several obvious limitations, which include low kinetic stability, suboptimal specific radioactivity, nonspecific accumulation in non-target tissues, and unknown coordination structure. 2 Therefore, significant efforts have been seen to develop bone seeking agents derivatized from bisphosphonates, in which the radiometal is coordinated by a “bifunctional chelator” that oftentimes carries a spacer to optimize the biological behavior. 2 In this regard, macrocyclic chelators are preferred over their acyclic counterparts because more kinetically stable complexes can result from their rigid and pre-organized structures.…”
mentioning
confidence: 99%
“…2 Therefore, significant efforts have been seen to develop bone seeking agents derivatized from bisphosphonates, in which the radiometal is coordinated by a “bifunctional chelator” that oftentimes carries a spacer to optimize the biological behavior. 2 In this regard, macrocyclic chelators are preferred over their acyclic counterparts because more kinetically stable complexes can result from their rigid and pre-organized structures. 36 Furthermore, macrocyclic ligands bearing a mixed set of phosphonate and carboxylate groups, such as TRITP, DOTP, DOA3P, and trans -DO2A2P (Figure 1), have been reported as novel bone targeting agents when labeled with radioisotopes (e.g.…”
mentioning
confidence: 99%
See 1 more Smart Citation